Fez & Sherwani: Consumption, Self-fashioning and Ottoman Influence in South Asia, 1826-1911 - Bamber, William (My University, 2022)
This dissertation examines how novel forms of ‘South-South’ transnational connection operating through image-print and popular consumption shaped a new ideal and aesthetics of modernizing manliness across a wide global geography during the later nineteenth century. It does so by tracing the rise and popularization across a swathe of late nineteenth century Asia of a particular style of male dress based around the fez and the long, high-buttoned coat known variously as the istanbulin or, in South Asia, sherwani. By documenting the origins, associations, and one particular trajectory of the fez and istanbulin/sherwani style’s travel, from Ottoman Istanbul to the Indian city of Hyderabad, it shows how ways of thinking about identity and belonging across nineteenth century Asia became reshaped by novel circuits of globalizing visual and material interaction, and the new opportunities for mass consumption. Drawing on over two years of fieldwork in archival, museum and library collections across Istanbul, Delhi, Hyderabad and London, it intervenes in debates around imperialism, gender and social reform by showing how localized renegotiations of identity, far from being restricted to a dialectic of colonial civilization versus proto-national tradition, exploited the opportunities of mass consumption to index intensely varied visions of aspirational personal modernity. As the popularization of a non-European, Ottoman style illustrates, changing constructions of urban class and gender were intrinsically transnational, formed in close relation to new epistemologies of global political knowledge, and a contemporaneously emerging globalizing aesthetics of urbane masculinity. While the fez and istanbulin/sherwani style was widely adapted across different groups and contexts to invoke different shades of association, its straight-lined symmetry and manly seriousness evoked a striking contrast with both more ornate earlier nineteenth century styles, and European-imperial male dress. Its adoption among many Jews, Christians, Hindus and varied other sects, moreover, problematizes generalizing paradigms like ‘pan-Islam’ by showing how claims to participation in a cosmopolitan global modernity cut across communal lines. The dissertation brings together debates from art, transnational and literary history by highlighting novel of forms ‘South-South’ visual and material connectivity enabled by everyday technologies like the camera, lithographic press and sewing machine. Expanding transnational history’s stress on trade and migration to emphasize movements of ideas and aesthetics, it explores how the development of a nascent global visual sphere operating through illustrated journals, photos and popular portraiture dramatically reshaped imaginations of the world among the non-travelling majority in Ottoman and Indian cities from the 1870s on. The transnational spread of Ottoman styles was predominantly a phenomenon of localized imitation rather than physical exchange, illustrating the power of imagery to generate internationalist identification. While histories of print and nationalism have emphasized literary-lingual communities, this project highlights the openness and ambiguity of visual transnationalism, and its close interrelation with material experience. This is exemplified by the fashion’s evolution in the South Indian city of Hyderabad, where it became adapted to local fabrics and material sensibilities to emerge as the emblem of an assertively localized ideal of manliness and revitalized South Indian-Deccani regional identity.
Thesis (Ph.D.)--University of Washington, 2022
Keywords: Fez; Hyderabad; Masculinity; Ottoman Fashion; Sherwani; Visual transnationalism; History; Near and Middle Eastern Studies